Learning achievement, Science process skills and scientific mind of matthayomsuksa 5 students by inquirycle learning management (7E) - Sarabut, Ruedeerat; Julsiripong, Sittisak; Keeratichamroen, Wasana (Ratchaphruek Journal, 2014)
The purposes of this research were 1) to study learning achievement on light unit using Inquiry Cycle Learning Management (7E), 2) to compare learning achievement on light unit before and after using Inquiry Cycle Learning Management (7E), 3) to compare learning achievement on light unit after using Inquiry Cycle Learning Management (7E) against the 70% criterion, 4) to study science process skills by Inquiry Cycle Learning Management (7E), 5) to compare science process skills before and after using Inquiry Cycle Learning Management (7E), 6) to study scientific mind by Inquiry Cycle Learning Management (7E) and 7) to compare scientific mind before and after using Inquiry Cycle Learning Management (7E). The samples were 22 students of Matthayomsuksa 5/1 of Nongbunmakprasongwittaya School who studied in the first semester of academic year 2012. The research tools were inquiry cycle lesson plans, achievement test, science process skills assessment and scientific mind assessment. Data was analyzed with statistical methods to find the percentage, mean, standard deviation and t-test. The results revealed that learning achievement on light unit, science process skills and scientific mindafter using Inquiry Cycle Learning Management were statistically significant higher than before using Inquiry Cycle Learning Management in all aspects at the .05 level. Learning achievement on light unit after learning by Inquiry Cycle Learning management was statistically significant lower than 70% criteria at the .05 level.